Development and study of biological coating materials for enhancement of host-graft interfacing affinity and biocompatibility - Tao, Chao (Nanyang Technological University, 2020)
Extracellular matrix (ECM) based grafts are promising in tissue regeneration since ECM is a hospitable 3D microenvironment for cells to adhere and proliferate. However, there are two issues that need to be addressed for clinical translation of ECM based grafts including immunocompatibility of xenografts and interfacing affinity of grafts with host tissues. In this thesis, we proposed a novel and facile method by coating natural biological materials to furnish the grafts with functions such as immune evasion or adhesion. For ECM based xenografts, autologous red blood cell (RBC) membrane or stabilized albumin coatings were investigated for attenuation of immune and inflammatory responses. Cell membrane is embedded with macromolecules such as sugars and proteins that govern cell functions or interactions including self-recognition. Autologous cell membrane coating could function as a disguise on xenografts which will be recognized as “self” by the host. Therefore, the host immune system will not attack the implants with autologous cell membrane as a disguise. RBC was chosen due to its abundance in human bodies. On the other hand, inflammation was initiated by absorption of proteins on foreign bodies. From this perspective, albumin could be used due to its passivation nature on xenografts to eliminate absorption of other proteins. In this case, the delivery of signals is hindered, which will affect the induction of immune and inflammatory responses. In this thesis, porcine-source living hyaline cartilage graft (LhCG), which contains mainly porcine chondrocytes and ECM, and decellularized LhCG (dLhCG), which is composed of porcine derived ECM, were chosen as xenograft models. Both autologous cell membrane disguise coating and stabilized albumin passivation coating were stable on grafts and showed better immunocompatibility on cell, protein and gene levels with less inflammatory cells involving neutrophils, macrophages and lymphocytes recruited and lower inflammation-related gene expression level. It is worth noting that in order to enhance adhesion of albumin on xenografts mentioned above, a mussel inspired adhesive, dopamine, was grafted on albumin. Dopamine is popular as a tissue adhesive, the catechol groups on which could form chelating bonds with metal ions. Inspired by this dopamine modified albumin coating on ECM based grafts, we considered developing an adhesive coating on ECM based grafts which could crosslink in situ with ferric ions for fixation with surrounding tissues after implantation. Therefore, dLhCG with dopamine based natural biological materials coatings was manufactured to address the interfacing affinity issue between dLhCG and cartilage. A macromolecules backbone was needed for the coating material to avoid the formation of a rigid crosslinking system and cytotoxicity caused by dopamine monomers. In this thesis, chondroitin sulfate (CS), a cartilage derived sulfated GAG, was chosen as backbone to fabricate dopamine modified CS (CSD) with no impurities introduced to joint. Dopamine modified serum albumin (BCD) was also chosen for comparison. Both dLhCG coated with CSD and dLhCG coated with BCD showed enhanced adhesive strength with cartilage after chelating with ferric ions in situ compared to dLhCG and further potential in improving interfacing affinity of dLhCG with cartilage. However, CSD coated dLhCG is superior in stronger adhesive strength at optimized working concentration, better performances in cell migration and no impurities introduced in joint. In summary, in this thesis, natural biological materials were investigated on ECM based grafts as functional coatings for enhanced immunocompatibility or interfacing affinity with surrounding host tissues.